Governing the justice system: Spain’s judicial council - (:unkn) unknown (My University, 2016)
Following the European model, many developing and transition economies have established councils independent of other government branches to govern their judiciaries. Spain’s experience illustrates the issues raised by the creation andoperation of these entities.